2018
DOI: 10.1534/genetics.118.301004
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Demethylase KDM5 Is Essential for Larval Growth in Drosophila

Abstract: Regulated gene expression is necessary for developmental and homeostatic processes. The KDM5 family of transcriptional regulators are histone H3 lysine 4 demethylases that can function through both demethylase-dependent and -independent mechanisms. While loss and overexpression of KDM5 proteins are linked to intellectual disability and cancer, respectively, their normal developmental functions remain less characterized. Drosophila melanogaster provides an ideal system to investigate KDM5 function, as it encode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 79 publications
5
38
0
Order By: Relevance
“…Demethylase-independent functions of KDM5 proteins have been described, but mostly in context with gene activation. For example, studies in D. melanogaster showed that loss of the essential KDM5 homolog Lid ( l ittle i maginal d iscs ) results in retarded larval development (Li et al, 2010), and this delay is independent of the histone demethylase activity encoded by the JmjC domain, suggesting that other domains of Lid are critical during early developmental processes (Drelon et al, 2018). Furthermore, functions in gene regulation that are independent of the catalytic activity are not restricted to KDM5 homologs or histone demethylases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demethylase-independent functions of KDM5 proteins have been described, but mostly in context with gene activation. For example, studies in D. melanogaster showed that loss of the essential KDM5 homolog Lid ( l ittle i maginal d iscs ) results in retarded larval development (Li et al, 2010), and this delay is independent of the histone demethylase activity encoded by the JmjC domain, suggesting that other domains of Lid are critical during early developmental processes (Drelon et al, 2018). Furthermore, functions in gene regulation that are independent of the catalytic activity are not restricted to KDM5 homologs or histone demethylases.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin is composed of histones and chromatin-associated factors. Histones are modified by posttranslational chemical modifications (e.g., acetylation, methylation, or phosphorylation) on different residues, and a certain combination of these histone marks generates a recognition platform for chromatin regulators that strongly influence how the underlying genetic information is read (Jenuwein, 2002; Wood et al, 2005; Drelon et al, 2018). The combination of histone PTMs defines the overall chromatin structure and transcriptional activity at a given genomic region.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster offers a genetically amenable model for providing fundamental insight into KDM5 function in vivo, as it encodes a single, highly conserved, kdm5 gene (Gildea et al, 2000). Moreover, in contrast to knockouts of KDM5A, KDM5B or KDM5C in mice that are homozygous viable, loss of Drosophila kdm5 results in lethality (Albert et al, 2013;Drelon et al, 2018;Iwase et al, 2016;Klose et al, 2007;Martin et al, 2018). This allows us to dissect crucial functions of KDM5 without the complication of functional redundancy between mammalian KDM5 paralogs that could partially occlude phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In their transcriptome analysis (based on microarrays) of lid KD wing imaginal discs, Azorin and colleagues found a similar number of differentially-expressed genes, most of them being downregulated [14]. However, RNA Seq analyses recently published by Drelon et al in contrast found 1630 genes (FDR<0.05) dysregulated in wing discs from a null lid mutant [26]. Moreover, Liu and Secombe [27] found 8,056 genes differentially expressed (60% were down-regulated) in lid adult mutant flies (FDR<0.05), a number which could reflect the greater cell type complexity involved in this analysis.…”
Section: Transcriptomic Analysis Of Lid Kd and Sin3a Kd Ovaries Identmentioning
confidence: 96%
“…At first, the paradoxical loss of H3K4me3 enrichment on the dhd gene upon Lid depletion suggests that the demethylase activity of Lid is not locally responsible for this regulation. In fact, it has been established that lid mutant females with a catalytic dead JmjC � lid rescue transgene are viable and at least partially fertile [23,26,31], thus suggesting that the catalytic activity of Lid is not absolutely required to form a viable zygote. To directly test the implication of the Lid demethylase domain in dhd regulation, we measured dhd expression in JmjC � rescued females.…”
Section: Impact Of Lid Depletion On the Distribution Of H3k4me3 In Ovmentioning
confidence: 99%